2023
DOI: 10.1093/ced/llad070
|View full text |Cite
|
Sign up to set email alerts
|

Dermatological adverse drug reactions to tyrosine kinase inhibitors: a narrative review

Abstract: Tyrosine kinase inhibitors (TKIs) target the signal transduction pathways of protein kinases by several modes of inhibition. Adverse effects are generally dose-dependent, with certain side effects unique to each drug. However, due to similarities in target sites, different classes of TKIs may have identical or overlapping side effect profiles. This narrative review is an attempt to summarize the common and uncommon adverse effects of different classes of tyrosine kinase inhibitors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 89 publications
0
3
0
Order By: Relevance
“…However, hypopigmentation was only reported once among patients receiving non‐imatinib TKIs in our review 16 . While hypopigmentation is a well‐known adverse effect of imatinib, it has also been seen with other TKIs not used for CML, such as cabozantinib and pazopanib 17 . Additionally, alopecia was only reported in two patients, both of whom received imatinib.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…However, hypopigmentation was only reported once among patients receiving non‐imatinib TKIs in our review 16 . While hypopigmentation is a well‐known adverse effect of imatinib, it has also been seen with other TKIs not used for CML, such as cabozantinib and pazopanib 17 . Additionally, alopecia was only reported in two patients, both of whom received imatinib.…”
Section: Discussionmentioning
confidence: 77%
“…TKIs not used for CML, such as cabozantinib and pazopanib. 17 Additionally, alopecia was only reported in two patients, both of whom received imatinib. Interestingly, our review's most frequently reported skin reaction was unspecified rash (67%, 133/199).…”
Section: Discussionmentioning
confidence: 99%
“…. Nevertheless, drug resistance and frequent relapse and associated adverse effects, including cardiovascular as major along with pulmonary and gastrointestinal disturbances, neuropathies, stomatitis, nasal bleeding, retinopathy, edema, dry skin, pruritis, pancreatitis, and hepatitis, remained as few to name as major bottlenecks with the advanced TKI application for Ph+ leukemia complete remission. Currently, ponatinib is the only drug that remains the most potent against most of TKI’s resistant forms.…”
Section: Introductionmentioning
confidence: 99%